The 6R Principles of Biodiversity Conservation and Protection: Arresting the Rate of Extinction and Major Threats to Wildlife in Indonesia - Hadi, Nestiyanto (Jurnal Green Growth dan Manajemen Lingkungan, 2023)
Indonesia is one of the countries that has a high level of biodiversity in the world. Indonesia's high level of biodiversity is influenced by several environmental carrying capacity factors such as rainfall, climate, temperature, topography, humidity, soil fertility and light intensity. Existing biodiversity can affect the culture of Indonesian society, especially in terms of utilizing natural materials in meeting daily needs. The existence of anthropogenic activities can have an impact on existing biodiversity, especially activities that do not follow applicable rules and regulations such as excessive hunting, illegal trade in endangered species, waste pollution and habitat conversion. If there is no effort to take conservation and protection measures, it will have an impact on the decline in population numbers to the extinction of species. Therefore, the 6R principles of conservation, which include release, relocation, reproduction, restocking, rehabilitation and research, need to be considered and implemented in the community. The 6R principle has been widely applied by researchers, governments and non-governmental organizations both at the broad scale of the ecosystem landscape and the small scale of the species level. Based on research activities, it is hoped that the 6R principle can scientifically become one of the efforts to reduce the extinction rate and the main threats to wildlife in Indonesia. In addition, the 6R principle can be a good thing to be developed in protected areas and become a lifestyle based on environmental insight in urban areas (urban conservation lifestyle).